Involving unused land in the economic turnover of the agricultural sector of a region: institutional regulation and economic feasibility - V. I. Trofimova (Вестник университета)
The article shows the necessity of institutional regulation of the process of involving unused agricultural land into the economic turnover of the agrarian sphere of a region. It presents quantitative and qualitative characteristics of previously withdrawn agricultural lands, their territorial distribution by soil and climatic microzones and administrative districts of a region, unused period duration, residual fertility level (in terms of humus content), and land plots degradation degree. A calculation-analytical complex such as an algorithm representing a four-stage mechanism of analysis, preparation and decision-making on the choice of the land plots restoration method and their further use option has been developed and proposed for use. It is recommended to use three options for land plots restoration: direct return to economic turnover in case of a short period of non-use; carrying out cultural and technical measures with subsequent implementation into the turnover; transfer to another category of use in case of a high degree of degradation and low fertility level. The developed algorithm of unused agricultural land involvement is aimed at preserving the land potential of a region, strengthening the rational land use system. The presented stages provide not only theoretical and methodological, but also practical significance. Application scope is scientific organizations, agroindustrial complex management bodies at the municipal and regional levels, and agricultural producers.